Mathematical simulation of turbulent mixing in a static mixer - Matvienko, Oleg V. (Journal of engineering physics and thermophysics)
Results of investigation of the turbulent mixing of liquid flows in a static mixer are presented. It was established that, in the case where liquids inflow into such a mixer with equal velocities, their movement in the radial direction in the mixer is absent. In this case, the main mechanism providing the mixing of liquid flows in a static mixer is their molecular diffusion, and, therefore, the intensity of mixing of the liquid flows is low. An increase in the difference between the velocities of the liquid flows at the inlet of a static mixer leads to their turbulization, with the result that the mixing of the liquids is substantially intensified, and a homogenous distribution of their mass fractions in the mixture is attained at a smaller distance from the inlet cross section of the mixer. When the difference between the velocities of the liquid flows at the inlet of a static mixer is large, at the center of the mixer channel there arises a recirculation flow zone in which the liquids are mixed intensively.